Pests and diseases of Ficus sp. in Malaysia - Ahmad Azmi, Nur Sabrina; Abdul, Nurul Huda; R, Nurul Wahida (Noor Publishing, 2021)
Nowadays, the value of fig cultivation in Malaysia increases as many species of Ficus grown as an ornamental in urban landscapes and popular indoor plants for the hobbyist or as a commercial production for fruit and planting material (cuttings, bareroots etc). However, Ficus plants are susceptible to diseases and pests such as anthracnose, Botrytis blight, gray mold, fig rust, Cercospora leaf spot and fruit rot. Furthermore, they are also prone to the attack by xylaphagous insects, sap sucking insects and plant eating insects. Therefore, maintaining healthy Ficus flora becomes a great challenge especially from sudden outbreaks of pests and pathogens. Hence, this chapter will describe the major pests and diseases in fig cultivation in Malaysia.